A Questão da Juventude na Contemporaneidade: Estudo dos Projetos de Vida em Arroio do Tigre/RS - Alessandra Troian (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2018)
Recognizing the importance of youth and that it has important role in rural development process, the objective of the study is to identify the life projects of young people children of family farmers producing tobacco in Arroio do Tigre/RS. Methodologically research is characterized as qualitative, the techniques used for data collection were: documental and bibliographic research, semi-structured interviews with 18 young people aged 14-25 years, as well as participant observation and field notebook. Analytically research was based on oriented perspective to Actors and Possibilities Court, Norman Long and Van der Ploeg and Gilberto Velho, respectively. The main results are lists, the fact that young people project their lives in rural areas, have a wide range of plans and actions, and it is emphasized that the same are optimistic about the realization of their life projects.